2018
DOI: 10.3390/rs10040507
|View full text |Cite
|
Sign up to set email alerts
|

HY-2A Altimeter Data Initial Assessment and Corresponding Two-Pass Waveform Retracker

Abstract: The accuracy and resolution of the marine gravity field derived from multisatellite altimeter data sets mainly depend on the corresponding range precision and spatial distribution. Here, we preliminarily investigate the performance of HY-2A altimeter data by analyzing cross-mission sea surface height discrepancies with SARAL/AltiKa and calculating correlation coefficients with respect to tide gauge measurements. We also explore the improved range precision that can be achieved using a two-pass weighted least s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…NC_A and NC_B denote the number of crossover points after and before deleting outliers, respectively. Unit: m. Compared to crossover statistic values in earlier HY-2A studies [18,19] for the ERM, the latest GM measurements stay at a consistent accuracy level with respect to ERM observations. A noticeable decrease in standard deviation (STD) values is observed for measurements within 1 day compared to those with no time limit.…”
Section: Data Analysis and Waveform Retrackingmentioning
confidence: 52%
See 3 more Smart Citations
“…NC_A and NC_B denote the number of crossover points after and before deleting outliers, respectively. Unit: m. Compared to crossover statistic values in earlier HY-2A studies [18,19] for the ERM, the latest GM measurements stay at a consistent accuracy level with respect to ERM observations. A noticeable decrease in standard deviation (STD) values is observed for measurements within 1 day compared to those with no time limit.…”
Section: Data Analysis and Waveform Retrackingmentioning
confidence: 52%
“…HY-2A started its geodetic mission in March 2016, and the revisiting period extended to 168 days from the original 14 days during exact repeat mission (ERM). has verified that HY-2A provides reliable measurements and shown that the two-pass waveform retracker enhances the range precision by a factor of 1.6 [18]. A previous study, conducted by Zhu et al (2019) indicated that HY-2A can provide similar marine gravity recovery to other altimeters on the basis of 1 Hz measurements [19].…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…The first was the integration of global shipboard sounding compilations, which are used to calibrate the predicted depths (Smith & Sandwell, ) and as ground‐truthed “pins” (e.g., Becker et al, ; Smith & Sandwell, ) to provide high‐resolution mapping where available. The second was the development of custom waveform picking algorithms, tuned for optimal sea surface slope recovery (e.g., Garcia et al, ; Sandwell & Smith, , ; Zhang & Sandwell, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%